Evaluasi Kepatuhan Pajak Berdasarkan Perilaku Data Keuangan dan Non Keuangan (Studi Kasus pada KPP Jakarta) - Maulana Muhammad, Bayu; Wirjolukito, Aruna (E-Jurnal Akuntansi; Vol 31 No 1 (2021), 2021)
The purpose of this research is to evaluate tax compliance based on the behavior of taxpayers' financial and non-financial data. This research is expected to be useful as material for evaluating the level of tax compliance of taxpayers. This study uses a case study method (single case) and uses a mixed method. Descriptive analysis is used to analyze data from the research object in the form of a single case unit analysis. The results of this study indicate the perceived behavior control of taxpayers that shows low tax compliance behavior. The combination of analysis of financial and non-financial data from taxpayers produces a useful evaluation in determining the level of tax compliance. Based on this, the low achievement of tax revenue realization and high tax audit performance is directly influenced by the low tax compliance behavior of taxpayers. Keywords: Tax Compliance; Behavior; Financial Data; Non-Financial Data.